Continuities and Disruptions in the High School Curriculum in the Province of Córdoba (1983–2023). Approaches to the Case of Citizenship Education (Itinerarios Educativos, 2025)
For the past decade, we have been studying the ways in which knowledge is approached in high school from both structural and pedagogical perspectives. In this article, we share partial results from the research project «Between Curriculum Policies and New Modalities of Schooling: The Relationship with Knowledge in High School», developed by the Faculty of Philosophy and Humanities at the National University of Córdoba. We analyze current curriculum policies for secondary education in the province of Córdoba, considering the mediations and articulations produced within the framework of national policies and agreements reached in the Federal Council of Education, as well as the processes of curricular recontextualization and institutionalization established by the province itself. The constructed periodization covers 1983 to 2023, allowing us to identify curricular continuities and disruptions within changes in the principles of selectivity and organization at the secondary level. Additionally, using citizenship education as a case study, we describe changes, continuities, and disputes over what and how to teach within different curriculum policies, and we examine teachers’ appropriation of these changes in scenarios of instability in curricular regulations.
Keywords: Curricular policies; secondary level; citizenship education; Córdoba curriculum